Digital Literacy Education and Cyber ​​Crime Mitigation Related to Online Gambling for Teenagers in Tanak Awu Village, Pujut District, Central Lombok Regency - Ahwan Ahwan; R. Fahmi Natigor Daulay; Lalu Panca Tresna D; Muhammad Rifaldi Setiawan; Fatahullah Fatahullah (Abdi Masyarakat, 2026)
The acceleration of information technology brings ambivalent impacts on rural youth, one of which is the high risk of exposure to negative content such as online gambling. youth groups in Tanak Awu Village, Central Lombok Regency, located in the buffer zone of Lombok International Airport, are vulnerable to digital culture shock and the criminogenic impacts of online gambling. This community service activity aims to strengthen youth's digital literacy through a preventive-educative approach based on cyber law. The methods applied were socialization and interactive lectures on the four pillars of digital literacy (digital skills, digital culture, digital ethics, and digital safety), followed by a regulatory review (the ITE Law and Law No. 1/2023 on the New Criminal Code), and evaluated through casual interviews. The result indicates a paradigm shift among the youths, from previously perceiving slot gambling as a lawless "grey area" to gaining a rational legal awareness regarding cyber-criminal sanctions. Furthermore, this activity successfully crystallized collective commitments, including the establishment of a defensive legal shield, a peer support system, and shifting focus toward productive digital activities.